Preferential Solvation of 4-Carboxyl-2,6-dinitrophenylazohydroxynaphthalenes in Aqueous Dimethylformamide and Dimethylsulfoxide Binary Mixtures by UV-Visible Spectroscopy. (2019)
The objective of this study was to evaluate the influence of partly aqueous solvent mixtures on the solubility and azohydrazone equilibrium processes for a group of phenylazohydroxynaphthalenes, AZ-01, AZ-02, AZ-03, and AZ-04, whose applications as potential color additives and chemosensors have been demonstrated in previous studies. The UV-visible spectrum was acquired between 190-900 nm at concentrations of the dyes that precluded molecular aggregation for each dye in aqueous dimethylformamide and dimethylsulfoxide binary mixtures of varying compositions. The plots of E12 against mole fractions of the co-solvent showed deviation from ideality in the behaviors of the four dyes in the aqueous solvent mixtures. The solvation data were largely influenced by the structural chemistry of the dyes. In particular, AZ-01, which contains a free parahydroxyl group that can donate hydrogen to hydrogen bond acceptor solvents showed substantial bathochromic shifts in the aqueous DMF and DMSO mixtures as well as a local accumulation of the organic solvent in its solvation sphere. Conversely, the positional isomer AZ-02 with its ortho hydroxyl group being involved in intramolecular hydrazone rearrangement exhibited dielectric enrichment in both aqueous solvent mixtures. In addition, synergism through formation of the water-DMSO and water-DMF complexes was observed with all the dyes in the solvent mixtures with AZ-01 being solvated by the more polar component of the complex while AZ-02 and AZ-04 were solvated by the less polar solvent mixture component. Thus, the preferential solvation of the phenylazohydroxynaphthalene series from AZ-01 to AZ-04 in the partly aqueous DMSO and DMF solvent mixtures has been successfully studied using UV-visible spectroscopy.